2019
DOI: 10.5194/hess-23-1505-2019
|View full text |Cite
|
Sign up to set email alerts
|

Predicting floods in a large karst river basin by coupling PERSIANN-CCS QPEs with a physically based distributed hydrological model

Abstract: In general, there are no long-term meteorological or hydrological data available for karst river basins. The lack of rainfall data is a great challenge that hinders the development of hydrological models. Quantitative precipitation estimates (QPEs) based on weather satellites offer a potential method by which rainfall data in karst areas could be obtained. Furthermore, coupling QPEs with a distributed hydrological model has the potential to improve the precision of flood predictions in large karst watersheds. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 33 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…However, IMERG-ER is more recommended for real-time flood detection with shorter latency and a tendency of higher precipitation extremes (Zhi Li et al 2021). Precipitation Estimation from Remotely Sensed Information Using Artificial Neural Networks-Cloud Classification System (PERSIANN-CCS), which provides near-real-time precipitation estimates at 0.048 spatial resolution and a 30-min temporal resolution with 1-h latency (Hong et al 2004), is widely used for short-duration extreme precipitation analysis (Sadeghi et al 2021) and flood prediction (Li et al 2019). It is found that the PERSIANN-CCS QPEs suffer serious underestimations (Li et al 2019;H.…”
Section: ) Quantitative Precipitation Estimatesmentioning
confidence: 99%
“…However, IMERG-ER is more recommended for real-time flood detection with shorter latency and a tendency of higher precipitation extremes (Zhi Li et al 2021). Precipitation Estimation from Remotely Sensed Information Using Artificial Neural Networks-Cloud Classification System (PERSIANN-CCS), which provides near-real-time precipitation estimates at 0.048 spatial resolution and a 30-min temporal resolution with 1-h latency (Hong et al 2004), is widely used for short-duration extreme precipitation analysis (Sadeghi et al 2021) and flood prediction (Li et al 2019). It is found that the PERSIANN-CCS QPEs suffer serious underestimations (Li et al 2019;H.…”
Section: ) Quantitative Precipitation Estimatesmentioning
confidence: 99%
“…(2) Empirical equations developed for similar basins were used to obtain the rainfall infiltration coefficients for different karst landforms and the rock permeability coefficient. For example, the rock permeability coefficient was calculated based on an empirical equation from a pumping test in a coal mine in the study area (Li et al, 2019). (3) A tracer experiment was conducted in the study area (Gou et al, 2010) to obtain information on the underground river direction and flow velocity; for instance, underground karst conduits are well developed in the area and form an underground river approximately 5 m wide.…”
Section: Modelling Datamentioning
confidence: 99%
“…For example, the distributed groundwater model MODFLOW-CFPM1 requires detailed data regarding the distribution of karst conduits in the study area (Reimann and Hill, 2009). Another example is the Karst-Liuxihe model (Li et al, 2019); there are 15 parameters and 5 underground vertical structures in this model. Such a complex structure results in large modelling-data demands, and modelling in karst areas is extremely difficult.…”
Section: Introductionmentioning
confidence: 99%
“…In practical applications, only a representative measured flood is needed to optimize the model parameters, which can greatly improve the performance of the model. The use of refined confluence calculation methods and highefficiency parameter optimization technology has enabled the Liuxihe model to achieve good results in forecasting floods in small and medium-sized rivers and in reservoir inflow forecasting in China [43][44][45][46][47][48][49]. technology has enabled the Liuxihe model to achieve good results in forecasting floods in small and medium-sized rivers and in reservoir inflow forecasting in China [43][44][45][46][47][48][49].…”
Section: Liuxihe Modelmentioning
confidence: 99%